Eglė Selevičienė, Nijolė Burkšaitienė. Web-based Learning Technologies in the Studies of English for Specific Purposes in Higher Education - Kobylarek, Aleksander (Verbum, 2026)
-
Keywords: web-based learning technologies; English for Specific Purposes; Cmap Tools; higher education